A new species of Orthobula Simon, 1897 (Araneae: Trachelidae) from South America - Espejo, Yolanda M.g. Piñanez; Munévar, Ana; Kochalka, John A. (Zootaxa, 2022)
Orthobula Simon, 1897 is a group of very small litter-dwelling spiders with a tropical and subtropical distribution. The genus comprises 18 species, without any records in the Neotropical realm yet. Here we describe O. sudamericana sp. nov., distributed in Argentina and Paraguay. The new species appears to be most closely related to O. chayuensis Yang, Song and Zhu, 2003. The male also resembles O. charitonovi (Mikhailov, 1986). Orthobula sudamericana sp. nov. females differ from these species by the straight and parallel insemination ducts, and males by the centrally located, U-shaped sperm duct. Further, we summarize details on its natural history and habitat characteristics.